2010
DOI: 10.1007/s10571-010-9637-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Depleting Agent Batroxobin has a Beneficial Effect on Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis (MS) was characterized with widespread demyelination and axonal loss of central nervous system (CNS). Fibrinogen (fibrin) deposition was considered as one of the pathogenesis of MS. Therefore, we explored the effects of fibrinogen depleting agent batroxobin in experimental autoimmune encephalomyelitis (EAE) mice model. Our study showed that prevention and suppression with batroxobin significantly ameliorated clinical severity of EAE, reduced inflammatory cells infiltration, and demyelination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Immunofluorescence microscopy revealed positive staining for fibrin(ogen) in lumbar spinal cord sections. Distribution of fibrin(ogen) in spinal cord sections was consistent with previous data demonstrating fibrin in white matter of EAE mice (Yang et al 2011). Compared to vehicle control, there appeared to be reduced signal for fibrin(ogen) in WE thrombin-treatment (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Immunofluorescence microscopy revealed positive staining for fibrin(ogen) in lumbar spinal cord sections. Distribution of fibrin(ogen) in spinal cord sections was consistent with previous data demonstrating fibrin in white matter of EAE mice (Yang et al 2011). Compared to vehicle control, there appeared to be reduced signal for fibrin(ogen) in WE thrombin-treatment (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Such animal studies also suggest that anticoagulation with heparin (Chelmicka-Szorc and Arnason 1972; Lider et al 1989) or the direct thrombin inhibitor, hirudin (Han et al 2008) improve the outcome of experimental autoimmune/allergic encephalomyelitis (EAE). Likewise, complementary studies performed in fibrinogen-deficient mice (Akassoglou et al 2004) or fibrin depletion by prophylactic administration of anticoagulants (Paterson 1976) or the defibrinogenating agent batroxobin (Yang et al 2011) have suggested that fibrinogen is at least one of the thrombin substrates that drives EAE progression and severity. To date, however, randomized controlled clinical studies have not been conducted to explore the utility of anticoagulants in the treatment of MS.…”
Section: Introductionmentioning
confidence: 99%
“…However, under pathological conditions associated with BBB and BSCB disruption, these proteins extravasate into brain and spinal cord parenchyma (Ryu & McLarnon, ). Moreover, fibrinogen/fibrin deposition is often seen in tissue from MS patients (Yang, Tian, Wu, Huang, & Wu, ). Our results revealed significantly increased leakiness for both fibronectin (Figure e–g) and fibrinogen (Figure i–k) in spinal cord sections of Cx47KO EAE mice compared with Cx32KO and WT groups; quantitative analysis of both the fibronectin (Figure h) and fibrinogen (Figure l) signals at 12 and 24 dpi confirmed this.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, MS lesions have increased levels of PAI-1 and less fibrin degradation and, thus, more sustained fibrin deposition than normal control tissue (Gveric et al, 2003 ). Fibrin depletion provides protection in a wide range of MS mouse models (Paterson, 1976 ; Akassoglou et al, 2004 ; Adams et al, 2007 ; Yang et al, 2011 ; Davalos et al, 2012 ). Studies of other Plg cascade components also support the hypothesis that fibrin deposition is a major instigator of experimental autoimmune encephalomyelitis (EAE).…”
Section: Plasminogen Activation and Fibrin Degradation In Cns Inflammmentioning
confidence: 99%